Disseminated infection in a cat on long-term ciclosporin therapy and potential latent infection of an in-contact cat - Jade Webster; Francesco Marchesi; Danièlle Gunn-Moore; Hayley Haining; Alison E Ridyard (Journal of Feline Medicine and Surgery Open Reports, 2022)
Case summary An 8-year-old domestic shorthair cat receiving long-term ciclosporin treatment was evaluated for a history of weight loss and hyporexia. The main clinical finding was a cluster of enlarged mesenteric lymph nodes. Cytological examination of fine-needle aspirates showed granulomatous inflammation with abundant acid-fast bacilli. A diagnosis of Mycobacterium avium complex (MAC) infection was confirmed by PCR. The cat’s clinical condition deteriorated rapidly despite appropriate antibiotic treatment and it was euthanased 2 weeks after initial presentation due to development of severe paraparesis and ataxia. Post-mortem examination revealed granulomatous inflammation affecting multiple lymph nodes and other organs with intrahistiocytic acid-fast bacilli consistent with mycobacteria when stained using Ziehl–Neelsen stain. Another cat in the same household was screened for infection using the interferon gamma release assay (IGRA), with the result being consistent with infection by non-tuberculous mycobacteria (NTM), which includes MAC; however, it had no grossly detectable disease. Relevance and novel information This case report is an unusual presentation of disseminated MAC infection in a cat, which remains a rare diagnosis. Clinicians should be aware of unusual and rare presentations of this infection. The clinical findings, progression of disease and histopathology results add to the current clinical database for feline disseminated MAC infections. Another cat in the same household tested positive for NTM by IGRA without any gross disease. This was suggestive of latent MAC infection which, to our knowledge, has not been previously reported in an in-contact cat.